The Interoperability of Internet Gatekeeper Services - Damjan, Matija (Digital Platforms: Legal And Economic Challenges, 2024)
This paper presents a discussion of the interoperability requirements for gatekeeper services as set out in the Digital Markets Act (DMA). The term 'vertical interoperability' is used to describe the integration of different levels of the value chain, for example, ensuring compatibility between hardware and software. In contrast, 'horizontal interoperability' concerns the interoperability of interchangeable products and services, such as messaging applications. The paper analyses specific interoperability requirements and their implications for gatekeepers, including the need to ensure the portability of user data and to provide technical interfaces for interoperability. Furthermore, the author reflects on the wider legal and economic implications of the DMA's interoperability provisions. While interoperability can promote competition and innovation, it also raises questions about the optimal balance between standardisation and diversity in the digital economy.